Reliable and early diagnosis of bacterial blight in pomegranate caused by Xanthomonas axonopodis pv. punicae using sensitive PCR techniques - Pushpa Doddaraju (Nature Portfolio, 2019)
Abstract Bacterial blight caused by Xanthomonas axonopodis pv. punicae is a major disease of pomegranate. Bacterial blight drastically reduces the yield and quality of fruits, which are critical for pomegranate production. Precise and early diagnosis of bacterial blight is crucial for active surveillance and effective management of the disease. Symptoms based disease diagnostic methods are labor-intensive, time-consuming and may not detect disease on asymptomatic plants. DNA-based disease diagnostics using polymerase chain reaction (PCR) are reliable, precise, accurate and quick. PCR coupled with agarose gel electrophoresis (PCR-AGE), PCR coupled with capillary electrophoresis (PCR-CE) and real-time PCR (qPCR) were applied for the early and accurate diagnosis of bacterial blight in pomegranate. PCR-CE and qPCR were capable of diagnosing bacterial blight 6 to 10 days before symptom appearance, with detection limits of 100 fg and 10 fg of bacterial DNA respectively. However, conventional PCR-AGE detected pathogen at the onset of disease symptoms with a detection limit of 10 pg of bacterial DNA. qPCR detected bacterial blight in orchards that did not show any disease symptoms. Our data demonstrate that qPCR is more sensitive than other PCR methods along with being reliable for early diagnosis.